Politik Hukum Penambahan Dana Desa (Manabia: Journal of Constitutional Law, 2025)
This study examines how the legal politics of additional village funds in the second amendment to village law number 3 of 2024. The focus of this research is to discuss the legal politics of the addition of village funds, its mechanism and the legal consequences arising from the addition of village funds. The purpose of this study is to determine the legal politics of village laws and the legal consequences of the addition of village funds. This research uses doctrinal (normative) methods or literature studies, legislation, legal products and several doctrines derived from the development of legal science, this research combines various theories, ideas, and legal principles. The results of this study indicate that there are additional funds taken from regional transfer funds (on top) in stages sourced from the APBN. In article 72 paragraph 4 explains "At least 10%" and paragraph 2 "streamline village-based programs in an equitable manner and can be increased according to the ability of the state" in other words there is an addition but not all villages get it, only underdeveloped villages and fixed income payments paid through village accounts. In law enforcement, the village has been supervised by the Village Council (BPD), the Financial and Development Supervisory Agency (BPKP), the local government and the village community. The legal consequences arising from the addition of village funds are such as: increased financial resources, better financial management, stricter legal responsibility, massive village development, increased village autonomy and increased village community participation.
Keywords: Array; Array; Array